PENGEMBANGAN BAHAN AJAR MBS BERBASIS HOTS DALAM MENINGKATKAN KETERAMPILAN 4C MAHASISWA MELAKSANAKAN KEGIATAN PLP II DI SEKOLAH DASAR - Simanjuntak, Sorta; Sitohang, Risma (Universitas Negeri Medan, 2022)
The aims of this study were to: (1) develop HOTS-based SBM teaching materials to improve students' 4C skills in learning at PGSD FIP Unimed. (2). validate product eligibility; (3) validating product practicality, and (4.) validating product effectiveness. This research method is the Research & Development method with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Data collection techniques were obtained from questionnaires, observation sheets and tests. The data analysis used descriptive techniques and continued with the inferential statistical test through the t test. Statistically, it was concluded that there was a significant difference in students' 4C skills in conducting PLP II at SD Mitra which pointed to an increase before and after the product was used in class F student learning at PGSD FIP with a 95% confidence level. Therefore the HOTS-based MBS teaching material module that was developed is very feasible, very practical and very effective to use to improve the 4C skills of PGSD FIP Unimed students in carrying out PLP II activities in elementary school through learning at PGSD.